Mechanisms of the antifungal action of marine metagenome-derived peptide, MMGP1, against Candida albicans. - Muthuirulan Pushpanathan; Paramasamy Gunasekaran; Jeyaprakash Rajendhran (PLoS ONE, 2013)
Background Development of resistant variants to existing antifungal drugs continues to be the serious problem in Candida albicans-induced fungal pathogenesis, which has a considerable impact on animal and human health. Identification and characterization of newer drugs against C. albicans is, therefore, essential. MMGP1 is a direct cell-penetrating peptide recently identified from marine metagenome, which was found to possess potent antifungal activity against C. albicans. Methodology/principal findings In this study, we investigated the mechanism of antifungal action of MMGP1 against C. albicans. Agarose gel shift assay found the peptide to be having a remarkable DNA-binding ability. The modification of the absorption spectra and fluorescence quenching of the tryptophyl residue correspond to the stacking between indole ring and nucleotide bases. The formation of peptide-DNA complexes was confirmed by fluorescence quenching of SYTO 9 probe. The interaction of peptide with plasmid DNA afforded protection of DNA from enzymatic degradation by DNase I. In vitro transcription of mouse β-actin gene in the presence of peptide led to a decrease in the level of mRNA synthesis. The C. albicans treated with MMGP1 showed strong inhibition of biosynthetic incorporation of uridine analog 5-ethynyluridine (EU) into nascent RNA, suggesting the peptide's role in the inhibition of macromolecular synthesis. Furthermore, the peptide also induces endogenous accumulation of reactive oxygen species (ROS) in C. albicans. MMGP1 supplemented with glutathione showed an increased viability of C. albicans cells. The hyper-produced ROS by MMGP1 leads to increased levels of protein carbonyls and thiobarbituric acid reactive substances and it also causes dissipation of mitochondrial membrane potential and DNA fragmentation in C. albicans cells. Conclusion And Significance: Therefore, the antifungal activity of MMGP1 could be attributed to its binding with DNA, causing inhibition of transcription followed by endogenous production of ROS, which triggers cascade of events that leads to cell death.